ANALYSIS OF ANXIETY LEVELS OF STUDENTS IN THE LEARNING PROCESS STATISTICS - Hendra Muharfi; Irma Aryani; Anzora Anzora; Asih Winarty; Meri Yulizar (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2024)
This study explores the level of mathematics anxiety during statistics learning among mathematics education students. Employing a qualitative approach, the research involved 21 students. Anxiety levels were measured throughout the learning process using a questionnaire comprising 30 statements and interviews based on three main indicators. Data were analyzed descriptively and categorized into three anxiety levels: high, moderate, and low. The results indicated that one student exhibited high anxiety levels, 13 students had moderate anxiety levels, and seven students had low anxiety levels